Creating systemic change through effective leadership - Fifth International Teaching for Intelligence Conference (Washington : SkyLight Professional Development, 1999)
The role of superintendents in effecting and sustaining meaningful change in the way schools deliver instruction is closely examined in this discussion of leading the restructuring process
Executive producer, Ela Aktay
Presenter: Gerald Lauber
Keywords: Educational leadership -- United States